SeDS: Secure Data Sharing Strategy for D2D Communication in LTE-Advanced Networks - Aiqing Zhang; Jianxin Chen; Qingyang Hu, Rose; Yi Qian (IEEE transactions on vehicular technology, 2016)
Security and availability are two crucial issues in device-to-device (D2D) communication, with its fast development in fourth-generation (4G) Long-Term Evolution Advanced (LTE-Advanced) networks. In this paper, we propose a secure data sharing protocol, which merges the advantages of public key cryptography and symmetric encryption, to achieve data security in D2D communication. Specifically, a public-key-based digital signature, combined with a mutual authentication mechanism of a cellular network, guarantees entity authentication, transmission nonrepudiation, traceability, data authority, and integrity. Meanwhile, symmetric encryption is employed to ensure data confidentiality. A salient feature of the proposed protocol is that it can detect free-riding attack by keeping a record of the current status for user equipment (UE) and realize reception nonrepudiation by key hint transmission between the UE and evolved NodeB, thus improving system availability. Furthermore, various delay models are established in different application scenarios to seek the optimal initial service providers (SPs) for achieving tradeoff between cost and availability. Extensive analysis and simulations demonstrate that the proposed protocol is indeed an efficient and practical solution for a secure data sharing mechanism for D2D communication.